GEORGIA IN RUSSIAN POLICY - SULABERIDZE, Yuri (CENTRAL ASIA AND THE CAUCASUS, 2007)
For a long time now, the Russian and Georgian political elites have been engaged in information warfare. It has even been seen to occur in cycles and produce noxious emissions at regular intervals, which poison the relations between the two countries. Today, the relations between the two sovereign states, which not so long ago belonged to the same country, are described using Cold War terms. I have not posed myself the task of going back to the history of Russian-Georgian relations: this would have called for a detailed analysis of the domestic reforms of the post-Soviet societies and the factors responsible for different vectors of their foreign policies. Mine is a more modest task: I have under-taken to identify the political myths still current in Georgian-Russian relations as well as the rea-sons for their viability. They come to the fore during periods when relations between the two countries worsen and mutual alienation and rejections take on radical tones. In search of the possible causes of mutual alienation, let us take a look into the past. We all know that one of the parts of the bipolar world disintegrated amid the failed perestroika reforms, because the “fathers of perestroika” did not realize that the convergence of two opposite systems and their coexistence within the “new thinking” of the communist and liberal ideologies were impossible. Under the global onslaught of liberalism, dogmatic Marxism had to retreat. The destruction of a system that could not respond to the challenges of the scientific and technological revolution raised an anti-wave that brought not only liberal-democratic ideas. The political elites of the young post-Soviet states were a weird symbiosis of Communist Party bureaucracy and nationalists. Radicalism, Anti-Sovietism, and anti-communism served as the soil on which the ideologies of national self-identification flourished.